Implementasi Bauran Pemasaran dalam Upaya Meningkatkan Keunggulan Bersaing pada Diuk Coffee and Eatery Purwakarta - Widiya Avianti; Mela Tri Yusnita (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2023)
This study aims to determine the marketing mix of Diuk Coffee and Eatery Purwakarta in an effort to increase competitive advantage. The method used in this study is qualitative descriptive, data collection techniques carried out using direct communication strategies, namely observation, interviews and documentation. The highest score of the SWOT matrix strategy combination score that was processed was in the Strenghts and Opportunities (SO) strategy with a total score of 4, this shows that Diuk Coffee and Eatery Purwakarta has considerable strength in developing businesses and has a competitive advantage with similar business actors in Purwakarta Regency. Therefore, the strategy (SO) carried out is to improve services to increase loyal customers, increase promotions by building online marketing applications and working with customers to provide offline testimonials (special boards for customer testimonials) and testimonials online, flexibility in physical supporting facilities by following trends in instagramable business places, and arranging café operational schedules for several events.